The significance of the Arabic sentence in the light of the mental perception theory (Journal of the College of Basic Education, 2023)
The subject of perception is quite a serious topic in his party and he did not address it as far as I knowThe humble is one of the educated or the respected writers in the Arab world at least, either from those who dealt with itThe Europeans have dealt with it in the narrowest limits, which are the limits of significance only, and this topic has lived with me sinceA long time ago when I watched (a movie) in one of the (cinemas) in the Egyptian city of Alexandria, and the name of the movieIt is the predatory jaw